2000
DOI: 10.1093/jn/130.11.2821
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Marginal Iron Intakes during Early Development in Mice Result in Persistent Changes in Dopamine Metabolism and Myelin Composition

Abstract: Marginal iron (Fe) deficiency is prevalent in children worldwide, yet the behavioral and biochemical effects of chronic marginal Fe intakes during early development are not well characterized. Using a murine model, previous work in our laboratory demonstrated persistent behavioral disturbances as a consequence of marginal Fe intakes during early development. In the present study, Swiss-Webster mice fed a control Fe diet (75 microgram Fe/g diet, n = 13 litters) or marginal Fe diet (14 microgram Fe/g diet, n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(94 citation statements)
references
References 63 publications
6
86
0
2
Order By: Relevance
“…Disruptions in iron processing, storage, or availability affect myelin quantity, quality, composition, and compaction (43,44), with alterations that persist even if the iron content of the myelin achieves normal levels after iron supplementation (45). As suggested previously in the same sample (4), the slower transmission in both auditory and visual systems likely arises from iron's role in myelination.…”
Section: Discussionmentioning
confidence: 67%
“…Disruptions in iron processing, storage, or availability affect myelin quantity, quality, composition, and compaction (43,44), with alterations that persist even if the iron content of the myelin achieves normal levels after iron supplementation (45). As suggested previously in the same sample (4), the slower transmission in both auditory and visual systems likely arises from iron's role in myelination.…”
Section: Discussionmentioning
confidence: 67%
“…The cytokine-mediated effects on glucocorticoid secretion may be of special interest because it has been suggested that prenatal physiological stress triggered by high glucocorticoid levels can interfere with normal physiological and metabolic development (130,156). Activation of the innate immune system (in response to infection) also changes the maternal and fetal availability of several micronutrients, including iron and zinc, both of which are highly important for the normal development of peripheral and central organs (3,71,72,149). In the case of iron, it is well established that infection leads to a temporary depletion of iron in the infected host.…”
Section: Possible Mechanisms Mediating the Effects Of Maternal Infectmentioning
confidence: 99%
“…Myelin was isolated according to Kwik-Uribe et al (2000), and the lipid content was further analyzed as described for cerebrum.…”
Section: Isolation Of Myelinmentioning
confidence: 99%